The Teacher Belief in The Classroom Management During Pandemic Covid 19 at SMPN 2 Kulisusu - Ratni Ratni; Tri Indah Rusli; Isna Humairah (Jurnal Pendidikan dan Pengajaran, 2022)
The pandemic is changing all the ways of teaching where face-to-face meetings are turning online. All of these changes also affect the way teachers manage their classrooms. This study aims to determine teachers' beliefs in classroom management. This research is a qualitative research. The subject of this research is an English teacher at SMPN 2 Kulisusu. Research data collection uses 2 ways, namely observation and interviews. Data analysis in this study is based on the theory of Miles, Huberman & Saldana which applies 3 stages in analyzing data, namely data reduction, data presentation, and drawing conclusions. Based on data from observations and interviews, this study found that teacher belief in classroom management was obtained from teaching experience, experience participating in training outside of school, and student activities in class. Of all the factors that most dominantly influence teachers' beliefs is experience in teaching.